2020
DOI: 10.1155/2020/8625186
|View full text |Cite
|
Sign up to set email alerts
|

Nonpuerperal Uterine Inversion: What the Gynaecologists Need to Know?

Abstract: Introduction. Nonpuerperal uterine inversion (NPUI) is a rare clinical problem with diagnostic and surgical challenges. The objective of our study was to review the literature on NPUI and describe causative pathologies, diagnosis, and different surgical options available for treatment. Materials and Methods. A comprehensive literature review was carried out on MEDLINE and Google Scholar databases to look for NPUI using the term “non-puerperal uterine inversion,” and further went through the cross-references of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 123 publications
0
64
0
3
Order By: Relevance
“…There was no evidence of abnormalities in 9.9% of all cases [ 6 ]. A recent literature review concluded that malignancy was present in one-third of the reported cases [ 7 ]. This should be discussed with patients when choosing the type of surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of abnormalities in 9.9% of all cases [ 6 ]. A recent literature review concluded that malignancy was present in one-third of the reported cases [ 7 ]. This should be discussed with patients when choosing the type of surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…Herath et al 15 had reviewed the literature on nonpuerperal uterine inversion (NPUI) by collecting the data of published case reports from 1911 to September 2018. NPUI is a rare gynecological condition with diagnostic and surgical challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of nonpuerperal uterine inversion depends on the patient's desire for future fertility and the nature of the intrauterine prolapsed mass (benign or malignant). If future fertility is desired and malignancy is excluded, surgical procedures to reposition and preserve the uterus should be attempted [ 5 , 10 ]. Thus, there is a need for histologic diagnosis prior to definitive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The repositioning of the uterus to the exact anatomy is vital before proceeding to hysterectomy. It is assumed that hysterectomy would be technically easier on a normally positioned uterus as repositioning would restore normal anatomy most surgeons are familiar with [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%